2005
DOI: 10.1529/biophysj.105.059790
|View full text |Cite
|
Sign up to set email alerts
|

Cyanine Dyes as Intercalating Agents: Kinetic and Thermodynamic Studies on the DNA/Cyan40 and DNA/CCyan2 Systems

Abstract: The interaction of cyanines with nucleic acids is accompanied by intense changes of their optical properties. Consequently these molecules find numerous applications in biology and medicine. Since no detailed information on the binding mechanism of DNA/cyanine systems is available, a T-jump investigation of the kinetics and equilibria of binding of the cyanines Cyan40 [3-methyl-2-(1,2,6-trimethyl-4(1H)pyridinylidenmethyl)-benzothiazolium ion] and CCyan2 [3-methyl-2-[2-methyl-3-(3-methyl-2(3H)-benzothiazolylide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 52 publications
0
68
0
Order By: Relevance
“…This behaviour indicates that D is not able to push the intercalated dye out of the nucleotide cavities, otherwise a fluorescence increase would be observed at the wavelength of 500 nm at which only the D-DNA complex, which is formed according to binding mode 2, is fluorescent. Because it is demonstrated that Cyan40 is intercalated between the base pairs of DNA, [45] the binding mode 2 necessarily should correspond to an intercalative process. This hypothesis was confirmed by the unwinding assay as well as by CD experiments.…”
Section: Full Papermentioning
confidence: 99%
“…This behaviour indicates that D is not able to push the intercalated dye out of the nucleotide cavities, otherwise a fluorescence increase would be observed at the wavelength of 500 nm at which only the D-DNA complex, which is formed according to binding mode 2, is fluorescent. Because it is demonstrated that Cyan40 is intercalated between the base pairs of DNA, [45] the binding mode 2 necessarily should correspond to an intercalative process. This hypothesis was confirmed by the unwinding assay as well as by CD experiments.…”
Section: Full Papermentioning
confidence: 99%
“…The fact that ligand-DNA complexes are formed is detected from the changes in the absorption spectra of the ligand, due to addition of the biopolymer to the ligand solution [8][9][10][11]14]. The nature of the changes occurring in this case is shown in Fig.…”
mentioning
confidence: 99%
“…Pyrvinium exhibits a dark-red fluorescent color which yields a higher signal upon interaction with DNA [82,83]. This "light up" effect, the increase of fluorescence intensity upon intracellular binding, is a typical property of DNA intercalators [84,85].…”
Section: Pyrviniummentioning
confidence: 99%